Division of labor in pachycondyla striata Fr. Smith, 1858 (Hymenoptera: Formicidae: Ponerinae) - Silva-Melo, Adolfo da (2012)
Four colonies of the ant Pachycondyla striata were used to analyze the specie behavioral repertoire. Forty-six behavioral acts were recorded in laboratory. Here, we present the record the division of labor between the castes and the temporal polyethism of monomorphic workers. The queens carried out many of the behavioral traits recorded in this work however; they performed them less frequently compared to the worker. The workers activity involved chasing and feeding on fresh insects and usingthem to nourish larvae besides laying eggs in the C-posture, an activity also performed by queens, which is similar to that of wasps of the subfamily Stenogastrinae. The young workers were involved in activities of brood care, sexuate care, and nest maintenance, and the older workers were involved in defense, exploration, and foraging. © 2012 Adolfo da Silva-Melo and Edilberto Giannotti.